Rediscounting under aggregate risk with moral hazard - James T. E. Chapman; Antoine Martin (Federal Reserve Bank of New York, 2007)
In a 1999 paper, Freeman proposes a model in which discount window lending and open market operations have different outcomes—an important development because in most of the literature the results of these policy tools are indistinguishable. Freeman's conclusion that the central bank should absorb losses related to default to provide risk-sharing goes against the concern that central banks should limit their exposure to credit risk. We extend Freeman's model by introducing moral hazard. With moral hazard, the central bank should avoid absorbing losses, contrary to Freeman's argument. However, we show that the outcomes of discount window lending and open market operations can still be distinguished in this new framework. The optimal policy would be for the central bank to make a restricted number of creditors compete for funds. By restricting the number of agents, the central bank can limit the moral hazard problem. And by making agents compete with each other, the central bank can exploit market information that reveals the state of the economy.
Keywords: G20; E58; 330; payment systems; money; open market operations; discount window; Gesamtwirtschaftliche Liquidität; Zentralbank; Offenmarktpolitik; Diskontpolitik; Kreditrisiko; Moral Hazard; Theorie